2009
DOI: 10.1007/s00267-009-9309-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Wastewater Treatment Plant Effluents to Nutrient Dynamics in Aquatic Systems: A Review

Abstract: Excessive nutrient loading (considering nitrogen and phosphorus) is a major ongoing threat to water quality and here we review the impact of nutrient discharges from wastewater treatment plants (WWTPs) to United States (U.S.) freshwater systems. While urban and agricultural land uses are significant nonpoint nutrient contributors, effluent from point sources such as WWTPs can overwhelm receiving waters, effectively dominating hydrological characteristics and regulating instream nutrient processes. Population g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
236
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(249 citation statements)
references
References 108 publications
3
236
0
10
Order By: Relevance
“…In comparison, phosphate levels decreased roughly fourfold from around 2008 to later years. As wastewater treatment plants may produce both nitrogen and phosphate in their effluents 32 , it is possible that improvements in wastewater treatment, either in terms of facilities or wastewater treatment works management, may have contributed to the decrease in phosphate observed recently. The relatively unchanged N:P ratio in the years since 2009 supports the likelihood that decreases in both nutrients may have the same cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, phosphate levels decreased roughly fourfold from around 2008 to later years. As wastewater treatment plants may produce both nitrogen and phosphate in their effluents 32 , it is possible that improvements in wastewater treatment, either in terms of facilities or wastewater treatment works management, may have contributed to the decrease in phosphate observed recently. The relatively unchanged N:P ratio in the years since 2009 supports the likelihood that decreases in both nutrients may have the same cause.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus loads from urban areas entering freshwater resources have particularly received considerable attention of late 18 because primary and secondary treatment of wastewater removes very little phosphate 32 , and because South African wastewater treatment works do not focus on phosphorus removal 18 . In addition, a significant portion of the phosphorus in domestic wastewater derives from phosphate-containing laundry detergents 26,27 which in many other countries have been banned or limited.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high-conductivity leachate has been shown to flow from valley fills created during coal mining operations [6,18,24]. In contrast, mixtures are more likely to be dominated by Cl À when they are associated with winter road maintenance [28,29], brines from natural gas and coalbed methane operations [30], treatment of wastewater [31], and human and animal waste [23,32]. Ecological studies have shown that conductivity increases only slightly following clear-cutting and burning.…”
Section: Preceding Causationmentioning
confidence: 99%
“…In mined and unmined sites, the dominant cations are Ca 2þ and Mg 2þ , and anions are HCO À 3 and SO 2À 4 [6,38] from largely calcareous geology. This excludes sources dominated by NaCl including saline effluents from human and livestock wastes [23,31,32], road salt [28,29], and produced brines from gas extraction (A. Bergdale, personal communication U.S. EPA, Wheeling WV; Supplemental Data, Table S3) [2,30]. The median difference is very large; 99% of anions are HCO À 3 and SO 2À 4 in both mined and unmined sites, whereas >99% of the anions are Cl À in brines from gas extraction in Marcellus shales (Supplemental Data, Table S3).…”
Section: Preceding Causationmentioning
confidence: 99%
“…Ure). To simulate implementation of tertiary treatment the concentrations of SRP (represented by inorganic P) and Total Phosphorus (TP: inorganic plus organic fractions) in STW effluents were capped at 1.5 and 2.0 mg P/L respectively (Carey and Migliaccio, 2009), these levels representing a realistic compromise between currently-available technology and avoiding expenses that are disproportionate for small treatment works. The effect of the measure was to cap the P content in over 85% of the total effluent volume discharging into the Swale system.…”
Section: Scenario Analysismentioning
confidence: 99%